Systems of Evaluation and the Matthew Effect. (October 2018) - Sauder, Michael
Existing research on the Matthew Effect establishes that this dynamic can alter information flow and the distribution of rewards in ways that lead to cumulating advantages for high status actors. We know little, however, about how systems of evaluation, and especially variations in systems of evaluations, influence the expression and strength of these outcomes. Drawing on analyses of the effects of rankings on organizations, I consider how different evaluation contexts can change both audience perceptions about which organizations are award worthy and the definition of merit on which reward distributions are based.